Health impact awareness of consuming cocoa based product among bumiputera population in Kota Kinabalu / Noradilla Osman - Osman, Noradilla (2015)
The purpose of this project is to study the health impact awareness of consuming cocoa product among Bumiputera population in Kota Kinabalu. Cocoa is a natural agricultural crop. Cocoa products were produced after the beans gone through certain processes without any additives mixed. Cocoa Based Product in the market such as chocolate, cookies and wafer, candies and snack, ice cream, cakes and pastry, cereal and milk product. Since, the consumer awareness towards cocoa based product are still quite low judging, this research are conducted to know the finding, with highlights the objective which is to identify consumers knowledge on health impact awareness of consuming cocoa product, to identify consumers attitude towards the effect of consuming cocoa product and to analyze consumer acceptance on consuming cocoa product. The research is focusing on Bumiputera in Kota Kinabalu area only. Quantitative data collection method and the simple random sampling are used to aid the research. The target population is Bumiputera. 120 questionnaires will be distributed to the respondent and will be analysed by using the Statistical Product and Service Solutions (SPSS) software.